Corporate social responsibility, Greek entrerprises and non governmental organizations - Τσαρδανίδης Χαράλαμπος (The Greek Review of Social Research, 2015)
The economic crisis has pushed many enterprises to consider seriously that cooperation with the NGOs is valuable in order to implement successfully their programs of Corporate Social Responsibility (CSR) as in recent years many companies has been engaged in various activities of the social life and the public sphere. The first part of the article analyses the relationship of the NGOs with companies in the framework CSR. The second part examines the outcomes of a survey which was conducted in order to find out to what extent the partnerships between Greek NGOs and companies in CSR programs was successful or not.